EFFECT OF TEMPERATURE AND HUMIDITY IN SOIL CARBON DIOXIDE EMISSION - M. F. Dilekoğlu; E. Sakin (Journal of Animal and Plant Sciences, 2017)
Carbon dioxide (CO2) emissions from terrestrial ecosystems have a global impact, and one of the most important of these is the greenhouse effect. Results demonstrated that the highest CO2 emissions were observed in apple cultivated fields, the least were found in cultivated land. The soil CO2 emission was measured as 54.47 g CO2 m-2 week-1 when the soil temperature was maximum (39.54°C) and the soil moisture was minimum (1.46%) and when the soil temperature was minimum (5.20 ° C) and soil moisture was maximum (18.77%) soil CO2 emissions was measured 49.89 g CO2 m-2 week-1. Soil CO2 emission was 36.98 g CO2 m-2 week-1 at the point where the soil moisture was maximum (29.93 %) and the soil temperature was 9.47 °C. Soil CO2 emission was at its maximum (74.04 g CO2 m-2 week-1) where soil temperature was 31.95 °C and soil moisture was 6.10 %.
Keywords: PVC container; CO2 emissions; soil respiration; greenhouse effect